'Why can't I grow shorter, only taller?'—the body experience of growing up for Chinese children aged 5–6. Issue 3 (September 2022) - Su, Yinshan; Chen, Yuejia; Huang, Jin
The body is the very basis of children's self-growth and their understanding of the world. However, children's body experiences of growing up have rarely been studied. This paper uses a hermeneutic phenomenological approach to study the body experience of 35 kindergarten children aged 5–6 from Nanjing, China. We found that children's body experiences can be grouped into two themes: the experience of body through physical changes, that is, children's experience of their physical changes; and the experience of body through actions, that is, children's experience of using their bodies to learn different skills and knowledge. Children's body experiences are multi-dimensional, ambivalent, and socially interactive throughout different events growing up. Even the same event involves multiple and contradictory experiences, which are influenced by both internal and external sources. Suggestions are discussed to address the problem of children's body experiences being neglected by adults.